Zinc oxide / silver nanoparticle loaded polystyrene composite nanospheres, their preparation and use in catalytic degradation of p-nitrophenol

CN118649708BActive Publication Date: 2026-10-13QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410757284.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2026-10-13
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

但使用单一催化剂存在催化性能欠佳的问题

Benefits of technology

[0036]1、本发明单分散聚乙烯吡咯烷酮-苯乙烯-丙烯酸纳米球(PS/PVP)的制备及其对ZnONPs和AgNPs的负载实验简单,所得聚乙烯吡咯烷酮-苯乙烯-丙烯酸纳米球具有优良的粒径均一性,其表面富含羧基基团,在分散体系中可通过静电排斥防止颗粒之间的小规模团聚,具有良好的分散性。PS/PVP纳米球表面的吡咯烷酮环和羧基基团使其成为ZnONPs和AgNPs的优良载体,得到的复合纳米球可作为NaBH4还原降解4-NP的高效催化剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004889852300000011
    Figure HDA0004889852300000011
  • Figure HDA0004889852300000012
    Figure HDA0004889852300000012
  • Figure HDA0004889852300000013
    Figure HDA0004889852300000013
Patent Text Reader

Abstract

The application provides a kind of zinc oxide / silver nanoparticle loaded polystyrene composite nanospheres and its preparation and application in catalytic degradation of p-nitrophenol.The preparation method of the application comprises the following steps: dissolving initiator and polyvinylpyrrolidone in deionized water, adding styrene and acrylic monomer, dispersing thoroughly, then polymerizing, drying to obtain nanospheres; then dispersing thoroughly in anhydrous ethanol, adding Zn source, mixing uniformly, adding reducing agent, reducing, centrifuging and washing to obtain zinc oxide loaded nanospheres; then dispersing thoroughly in anhydrous ethanol, adding Ag source, mixing uniformly, adding reducing agent, reducing, centrifuging, washing and drying to obtain the product.The composite nanosphere catalyst of the application is suitable for catalytic degradation of p-nitrophenol in water, has high degradation efficiency, can catalyze 99% of 4-NP to be degraded by sodium borohydride within 10s under sunlight, and has good recycling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of p-nitrophenol degradation, specifically relating to a polystyrene composite nanosphere supported by zinc oxide / silver nanoparticles, its preparation, and its application in the catalytic degradation of p-nitrophenol. Background Technology

[0002] Water pollution caused by various pollutants is becoming increasingly serious, among which nitroaromatic compounds are of particular concern due to their inherent toxicity, teratogenicity, and carcinogenicity. On the one hand, their excellent water solubility means that even trace amounts of nitroaromatic compounds can affect water transparency and the survival of aquatic plants and animals, leading to deeper water pollution. On the other hand, the structural stability of nitroaromatic compounds makes them extremely difficult to degrade, thus making them more likely to penetrate the food chain and accumulate in the human body, adversely affecting the central nervous system, liver, kidneys, and blood. p-Nitrophenol (4-NP) is even listed as a top-tier pollutant by the U.S. Environmental Protection Agency, and it is widely found in wastewater from pharmaceutical manufacturing, bactericides, pesticides, and dye industries. Therefore, the treatment of wastewater containing nitroaromatic compounds, especially p-nitrophenol, urgently needs further resolution.

[0003] For the removal of 4-NP, physical adsorption and sedimentation flocculation can be used to reduce the total amount of 4-NP in wastewater. However, these methods cannot completely remove 4-NP from the water, and the treatment of the resulting waste becomes another problem. It is worth noting that 4-NP can be converted into another less toxic or useful chemical, such as p-aminophenol (4-AP), which is a useful raw material for pesticides, dyes, and cosmetics. Therefore, the conversion of 4-NP to 4-AP is a key issue. Electrolytic reduction, metal acid reduction, and catalytic hydrogenation can achieve this conversion, with catalytic hydrogenation being the most effective due to its high conversion rate and environmental friendliness. Sodium borohydride can be used as a hydrogen source for the catalytic hydrogenation reaction, but considering its low hydrogen release efficiency and the stability of 4-NP, a highly efficient catalyst is needed to catalyze the reduction of 4-NP.

[0004] Metal nanoparticles (NPs) are among the best catalysts for catalytic hydrogenation reactions, with AuNPs, AgNPs, PdNPs, and PtNPs all capable of acting as individual catalysts. However, using a single catalyst can lead to suboptimal catalytic performance. Furthermore, the high surface energy of nanoparticles makes them prone to aggregation, resulting in a significant reduction in catalytic performance. To overcome this drawback, researchers typically immobilize nanoparticles on a support surface to increase their specific surface area and fully utilize the catalytic activity of NPs. Since factors such as the size and loading rate of NPs significantly affect catalytic efficiency, selecting a suitable support is crucial.

[0005] Therefore, how to prepare a metal nanoparticle catalyst that can effectively catalyze the degradation of p-nitrophenol is worthy of further research. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a polystyrene composite nanosphere supported by zinc oxide / silver nanoparticles, its preparation, and its application in the catalytic degradation of p-nitrophenol. The preparation method of the composite nanosphere catalyst of this invention is simple; the obtained composite nanosphere catalyst is suitable for the catalytic degradation of p-nitrophenol in water, exhibiting high degradation efficiency. It can catalyze the degradation of 99% of 4-NP by sodium borohydride (NaBH4) within 10 seconds under sunlight conditions, and also possesses good recyclability.

[0007] This invention is achieved through the following technical solution:

[0008] A polystyrene composite nanosphere supported by zinc oxide / silver nanoparticles, wherein the composite nanosphere is a polyvinylpyrrolidone-styrene-acrylic acid nanosphere carrier with zinc oxide nanoparticles and silver nanoparticles loaded on the surface of the polyvinylpyrrolidone-styrene-acrylic acid nanosphere carrier and the surface of the zinc oxide nanoparticles; the polyvinylpyrrolidone-styrene-acrylic acid nanosphere is a styrene-acrylic acid copolymer nanosphere with polyvinylpyrrolidone coated on its surface.

[0009] According to a preferred embodiment of the present invention, the particle size of the polyvinylpyrrolidone-styrene-acrylic acid nanospheres is 180-220 nm.

[0010] The preparation method of the above-mentioned zinc oxide / silver nanoparticle-supported polystyrene composite nanospheres includes the following steps:

[0011] (1) Dissolve the initiator and polyvinylpyrrolidone (PVP) in deionized water, add styrene (St) and acrylic acid (AA) monomers, disperse them fully, and then polymerize and dry to obtain polyvinylpyrrolidone-styrene-acrylic acid nanospheres (PS / PVP);

[0012] (2) Polyvinylpyrrolidone-styrene-acrylic acid nanospheres were fully dispersed in anhydrous ethanol, Zn source was added, and the mixture was thoroughly mixed. A reducing agent was added, and after reduction reaction, centrifugation and washing were performed to obtain zinc oxide-loaded polystyrene composite nanospheres.

[0013] (3) The zinc oxide-loaded polystyrene composite nanospheres were fully dispersed in anhydrous ethanol, Ag source was added, and the mixture was thoroughly mixed. A reducing agent was added, and after reduction reaction, the mixture was centrifuged, washed, and dried to obtain zinc oxide / silver nanoparticle-loaded polystyrene composite nanospheres.

[0014] According to a preferred embodiment of the present invention, in step (1), the initiator is potassium persulfate (KPS); the mass of the initiator is 2-4% of the mass of styrene, preferably 3%.

[0015] According to a preferred embodiment of the present invention, in step (1), the mass of polyvinylpyrrolidone (PVP) is 0.01-0.06% of the mass of deionized water.

[0016] According to a preferred embodiment of the present invention, in step (1), the mass ratio of styrene, acrylic acid and polyvinylpyrrolidone (PVP) is 3-4:1:0.02-0.11.

[0017] According to a preferred embodiment of the present invention, in step (1), the polymerization reaction conditions are as follows: under inert gas protection and stirring, the polymerization reaction is carried out at 70-80°C for 10-14 hours, followed by a polymerization reaction at 85-90°C for 0.5-1 hours. Preferably, the inert gas is nitrogen or argon.

[0018] According to a preferred embodiment of the present invention, in step (2), the mass ratio of polyvinylpyrrolidone-styrene-acrylic acid nanospheres to the volume ratio of anhydrous ethanol is 0.01-0.1 g / mL.

[0019] According to a preferred embodiment of the present invention, in step (2), the Zn source is Zn(Ac)2·2H2O; the mass ratio of the Zn source to the polyvinylpyrrolidone-styrene-acrylic acid nanospheres is 0.06-0.1:1.

[0020] According to a preferred embodiment of the present invention, in step (2), after adding the Zn source, the mixture is stirred at 55-65°C for 0.5-2 hours to ensure thorough and uniform mixing, thereby ensuring that zinc ions are completely dispersed on the surface of the nanospheres.

[0021] According to a preferred embodiment of the present invention, in step (2), the reducing agent is a NaOH ethanol solution with a concentration of 55-60 mmol / L; the mass ratio of NaOH to zinc source is 0.4-0.5:1; and the reducing agent is added to the system dropwise.

[0022] According to a preferred embodiment of the present invention, in step (2), the reduction reaction temperature is 50-70°C, the reduction reaction time is 1-3 hours, and the reduction reaction is carried out under stirring conditions.

[0023] According to a preferred embodiment of the present invention, the mass ratio of polyvinylpyrrolidone-styrene-acrylic acid nanospheres in step (2) to the volume ratio of anhydrous ethanol in step (3) is 0.002-0.003 g / mL.

[0024] According to a preferred embodiment of the present invention, in step (3), the Ag source is AgNO3; the mass ratio of the Ag source to the mass ratio of the polyvinylpyrrolidone-styrene-acrylic nanospheres in step (2) is 1-3:1.

[0025] According to a preferred embodiment of the present invention, in step (3), after adding the Ag source, the mixture is stirred at room temperature for 2-4 hours to ensure thorough and uniform mixing, thereby ensuring that the silver ions are completely adsorbed on the surface of the nanospheres.

[0026] According to a preferred embodiment of the present invention, in step (3), the reducing agent is an ethanol solution of n-butylamine, wherein the volume ratio of n-butylamine to ethanol is 1:45-55; and the mass ratio of Ag source to reducing agent is 1-3:1 g / mL.

[0027] According to a preferred embodiment of the present invention, in step (3), the reduction reaction temperature is 40-60°C, the reduction reaction time is 1-3h, and the reduction reaction is carried out under stirring conditions.

[0028] The above-mentioned zinc oxide / silver nanoparticle-supported polystyrene composite nanospheres were used as catalysts for the catalytic degradation of p-nitrophenol (4-NP) in wastewater by NaBH4.

[0029] According to a preferred embodiment of the present invention, the catalytic condition is visible light irradiation.

[0030] According to a preferred embodiment of the present invention, the application method includes the steps of: fully dispersing the catalyst and sodium borohydride in wastewater containing p-nitrophenol (4-NP), and degrading p-nitrophenol under visible light irradiation.

[0031] Preparation and catalytic mechanism of the composite nanospheres of this invention:

[0032] This invention prepares carboxyl-functionalized PS / PVP nanospheres using an environmentally friendly water-dispersion polymerization method. The particle size uniformity of the nanospheres was improved by changing the feed ratio of styrene and acrylic monomers, and the dispersibility of the nanospheres was enhanced by reducing the concentrations of styrene and acrylic monomers in the system. Ultimately, PS / PVP nanospheres with high monodispersity were prepared as catalyst supports. Zinc ions were successfully loaded onto the PS / PVP nanospheres by using the PVP pyrrolidone ring complexation on the surface of the nanospheres followed by reduction with NaOH. Silver ions were successfully loaded onto the PS / PVP nanospheres by adsorbing them using the carboxyl groups on the surface of the nanospheres and then by in-situ reduction with n-butylamine. ZnONPs and AgNPs were co-loaded on the surface of the PS / PVP nanospheres to prepare a composite catalyst.

[0033] When exposed to visible light, electrons in AgNPs on the surface of PS / PVP nanospheres are excited to the conduction band (CB) of AgNPs via surface plasmon resonance (LSPR) and generate holes in the valence band (VB). These conduction band electrons positively influence the catalytic degradation of 4-NPs. When two materials with different work functions come into contact, a Schottky barrier is formed. The work functions of ZnO and Ag are 5.2 eV and 4.26 eV, respectively. The larger work function of ZnO leads to a higher Fermi level (F) in Ag. Ag The Fermi level (F) is higher than that of ZnO. ZnO During the formation of composite materials, electrons move from F... Ag Transfer to F ZnO The process continues until the two energy levels reach equilibrium and a new Fermi level is formed. AgNPs on the ZnONPs surface enhance electron-hole pair separation and reduce electron-hole pair recombination, resulting in more free electrons in the composite material at the new Fermi level. Under illumination by visible light photons with wavelengths equal to or greater than the band gap wavelength of the photocatalyst, electrons jump to the conduction band and generate holes in the valence band of ZnO. AgNPs and ZnO / AgNPs provide a large number of electrons for the catalytic degradation reaction, while BH4... - Hydrolysis in water provides a large amount of [H], and under the combined action of both, the nitro groups in 4-NP gradually transform into amino groups, generating 4-AP, thereby achieving the degradation of 4-NP.

[0034] The preparation method and conditions of the zinc oxide / silver nanoparticle-supported polystyrene composite nanospheres of this invention work together as a whole to prepare the polystyrene composite nanospheres with the structure and properties of this invention, which are loaded with ZnONPs and AgNPs. The ratio of styrene to acrylic acid in the preparation of the polystyrene nanosphere support must be appropriate; a small amount of acrylic acid will result in uneven particle size distribution of the polystyrene nanospheres, while an excessive amount of acrylic acid will cause severe adhesion of the polystyrene nanospheres. The amount of deionized water used in the water dispersion polymerization of this invention must be appropriate; as the amount of deionized water increases, the dispersion performance of the polystyrene nanospheres is improved. In the loading experiments of ZnONPs and AgNPs on PS / PVP nanospheres of this invention, the ratio of PS / PVP nanospheres to Ag source, the ratio to Zn source, the loading order of ZnONPs and AgNPs, and the raw material concentration all have a significant impact on the morphology and catalytic performance of the composite catalyst; unsuitable preparation conditions will not yield the polystyrene-based composite nanosphere catalyst with ZnONPs and AgNPs co-supported to the specific morphology and catalytic performance of this invention.

[0035] The beneficial effects of this invention are as follows:

[0036] 1. The preparation of monodisperse polyvinylpyrrolidone-styrene-acrylic acid nanospheres (PS / PVP) and their loading experiments on ZnONPs and AgNPs are simple. The obtained polyvinylpyrrolidone-styrene-acrylic acid nanospheres have excellent particle size uniformity, and their surface is rich in carboxyl groups. In the dispersion system, small-scale agglomeration between particles can be prevented by electrostatic repulsion, resulting in good dispersibility. The pyrrolidone rings and carboxyl groups on the surface of the PS / PVP nanospheres make them excellent supports for ZnONPs and AgNPs. The resulting composite nanospheres can serve as a highly efficient catalyst for the reduction and degradation of 4-NPs by NaBH4.

[0037] 2. The polystyrene composite nanospheres supported by zinc oxide / silver nanoparticles prepared in this invention can be used to catalyze the degradation of 4-NP in an aquatic environment. It does not require ultraviolet light conditions and can rapidly catalyze the degradation of most 4-NP under sunlight conditions. It has high degradation efficiency and can catalyze the degradation of 99% of 4-NP by sodium borohydride (NaBH4) within 10 seconds under sunlight conditions. It also has good recyclability. Attached Figure Description

[0038] Figure 1 SEM image (a), Zeta potential (b), and Malvern particle size analysis (c) of the PS / PVP nanospheres prepared in Example 1;

[0039] Figure 2 SEM image of the PS / PVP nanospheres prepared in Example 2;

[0040] Figure 3 SEM image of the PS / PVP nanospheres prepared in Example 3;

[0041] Figure 4 SEM image of the PS / PVP nanospheres prepared in Example 4;

[0042] Figure 5 SEM image (a), infrared spectrum (b), and X-ray diffraction pattern (c) of the PS / PVP@ZnO / AgNPs composite nanospheres prepared in Example 5;

[0043] Figure 6 SEM image of the PS / PVP@AgNPs composite nanospheres prepared in Comparative Example 1;

[0044] Figure 7 The degradation efficiency of NaBH4 on 4-NP under the action of no catalyst (a), PS / PVP@AgNPs catalyst (b), PS / PVP@Ag / ZnONPs catalyst (c), and PS / PVP@ZnO / AgNPs catalyst (d) is shown.

[0045] Figure 8 Color changes of the system before and after 10 s of the PS / PVP@ZnO / AgNPs-catalyzed degradation of 4-NP in NaBH4;

[0046] Figure 9 The diagram shows the cyclic experiment of the degradation of 4-NP by NaBH4 catalyzed by PS / PVP@ZnO / AgNPs. Detailed Implementation

[0047] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.

[0048] To enable those skilled in the art to better understand the technical solutions of this application, the technical solutions of the present invention will be described in detail below with reference to specific embodiments.

[0049] Example 1: Preparation of monodisperse polyvinylpyrrolidone-styrene-acrylic acid nanospheres (PS / PVP)

[0050] The preparation method steps are as follows:

[0051] Weigh 0.1 g of KPS initiator and 0.02 g of PVP (available from Aladdin, average molecular weight 58,000) stabilizer and dissolve in 195 mL of deionized water. Mechanical stirring (500 rpm) is started at room temperature, and N2 is introduced to eliminate the influence of oxygen. After deoxygenation for 30 minutes, 3.6 g of styrene (St) monomer and 1 g of acrylic acid (AA) monomer are added to the system, and stirring continues for 20 minutes to completely disperse the monomers. After complete dispersion, the system temperature is raised to 80 °C, and the reaction is carried out under N2 atmosphere for 12 hours to polymerize the monomers. After 12 hours of polymerization, the system temperature is further raised to 85 °C and reacted for 30 minutes to ensure all monomers participate in the polymerization reaction. After the reaction is complete, the system is cooled to room temperature to obtain a white PS / PVP nanoemulsion, which is then dried to obtain polyvinylpyrrolidone-styrene-acrylic acid nanospheres (PS / PVP).

[0052] SEM image of the PS / PVP nanospheres prepared in this embodiment ( Figure 1 a) This shows that the particle size is uniform and distributed at around 200 nm. At this point, the mass ratio of St to AA is 3.6:1. The polystyrene segments rapidly curl up due to hydrophobic interactions, while the polyacrylic acid segments provide carboxyl groups to provide electrostatic repulsion between the nanospheres, resulting in good dispersibility. (PS / PVP particle size distribution diagram) Figure 1 c) shows that its particle size is concentrated around 200 nm, which is consistent with the SEM image of PS / PVP. Furthermore, the zeta potential diagram ( Figure 1b) The PS / PVP surface is negatively charged, which is attributed to the carboxyl groups on its surface.

[0053] Example 2

[0054] The preparation of polyvinylpyrrolidone-styrene-acrylic acid nanospheres (PS / PVP) was as described in Example 1, except that the amount of styrene monomer used was 4.1 g and the amount of acrylic acid monomer used was 0.5 g; the other steps and conditions were the same as in Example 1.

[0055] SEM images of the polyvinylpyrrolidone-styrene-acrylic acid nanospheres prepared in this comparative example are shown below. Figure 2 As shown in the image, the particle size is not uniform, with smaller nanospheres around 50 nm in diameter and larger nanospheres reaching around 220 nm in diameter.

[0056] Example 3

[0057] The preparation of polyvinylpyrrolidone-styrene-acrylic acid nanospheres (PS / PVP) was as described in Example 1, except that the amount of styrene monomer used was 3.2 g and the amount of acrylic acid monomer used was 1.5 g; the other steps and conditions were the same as in Example 1.

[0058] SEM images of the polyvinylpyrrolidone-styrene-acrylic acid nanospheres prepared in this comparative example are shown below. Figure 3 As shown in the image, the nanospheres are deformed, with a particle size distribution of around 160 nm, but the nanospheres are severely adhered to each other.

[0059] Example 4

[0060] The preparation of polyvinylpyrrolidone-styrene-acrylic acid nanospheres (PS / PVP) was as described in Example 1, except that the amount of deionized water used was 95 mL; the other steps and conditions were the same as in Example 1.

[0061] SEM images of the polyvinylpyrrolidone-styrene-acrylic acid nanospheres prepared in this comparative example are shown below. Figure 4 As shown in the image, the nanospheres have a relatively uniform particle size, but poor dispersion, with adhesion between them.

[0062] As can be seen from Example 1 and its comparative examples, the optimal amount of styrene required to prepare PS / PVP nanosphere carriers is 4 mL, the optimal amount of acrylic acid is 1 mL, and the optimal amount of deionized water is 195 mL.

[0063] Example 5: Preparation of polystyrene composite nanospheres supported by zinc oxide / silver nanoparticles

[0064] The preparation method steps are as follows:

[0065] 0.1 g of the PS / PVP nanospheres prepared in Example 1 were ultrasonically dispersed in 3.5 mL of anhydrous ethanol. 0.008 g of Zn(Ac)₂·2H₂O was weighed and added to the system, and the temperature was raised to 60 °C. The mixture was stirred continuously for 1 h to ensure complete dispersion of zinc ions on the nanosphere surface. To reduce the zinc ions, 1.5 mL of a 58 mM NaOH ethanol solution was slowly added dropwise to the system under stirring. After the addition was complete, the system was stirred at 60 °C for another 2 h. After the reaction was complete, the system was cooled to room temperature, centrifuged to obtain an intermediate product, and washed several times with anhydrous ethanol to obtain zinc oxide-supported polystyrene composite nanospheres. Zinc oxide-supported polystyrene composite nanospheres were redispersed in 45 mL of anhydrous ethanol to form a new system. 0.2 g of AgNO3 was added to the system, and the mixture was stirred at room temperature for 3 h to ensure complete dispersion of silver ions on the surface of the nanospheres. 100 μL of n-butylamine (dissolved in 5 mL of anhydrous ethanol) was slowly added to the system under stirring. The system was heated to 50 °C and stirred continuously for 2.5 h. After the reaction was complete, the system was cooled to room temperature, centrifuged to obtain the product, washed several times with anhydrous ethanol, and dried in an oven to obtain zinc oxide / silver nanoparticle-supported polystyrene composite nanospheres (PS / PVP@ZnO / AgNPs).

[0066] The SEM image of the composite nanospheres prepared in this embodiment is shown below. Figure 5 As shown in Figure a. The image shows that the surface of the PS / PVP nanospheres is simultaneously loaded with both small-diameter and large-diameter nanoparticles. Infrared spectrum ( Figure 5 b) The infrared spectrum of the PS / PVP nanospheres shows characteristic absorption peaks for both styrene and acrylic monomers, confirming successful monomer polymerization; 2900 cm⁻¹ -1 The nearby new peaks originate from the stretching vibrations of saturated CH bonds in the polymer chain, further confirming the success of the polymerization reaction. In the infrared absorption spectrum of PS / PVP@ZnO / AgNPs, in addition to the same characteristic peaks as those of PS / PVP@AgNPs (prepared by the method in Comparative Example 1), additional peaks appear in the 400-600 cm⁻¹ range. -1 The strong absorption peaks around the left and right sides, attributed to the Zn-O bond vibrations in the ZnO crystal, demonstrate the successful loading of ZnONPs. XRD diffraction pattern of PS / PVP@ZnO / AgNPs ( Figure 5c) The XRD pattern shows distinct diffraction peaks at 38.25°, 44.21°, 64.71°, 77.43°, and 81.61°, corresponding to the (111), (200), (220), (311), and (222) planes, which are the crystal planes of the Ag face-centered cubic structure. The XRD pattern also shows small, visible diffraction peaks at 31.77°, 34.42°, 36.23°, 47.52°, 56.61°, 62.74°, and 68.76°, corresponding to the (100), (002), (101), (102), (110), (103), and (112) planes, characteristic of the hexagonal wurtzite ZnO crystal structure. The characteristic peaks of AgNPs and ZnONPs further confirm the formation of the composite nanospheres.

[0067] Comparative Example 1

[0068] To compare the catalytic performance of the materials, polystyrene composite nanospheres individually loaded with silver nanoparticles were prepared. The preparation method is as follows:

[0069] 0.1 g of the PS / PVP nanospheres prepared in Example 1 was weighed and ultrasonically mixed in 45 mL of anhydrous ethanol. 0.2 g of AgNO3 was added, and the mixture was stirred at room temperature for 3 h to ensure complete adsorption of silver ions onto the surface of the microspheres. In-situ reduction of the silver ions was performed by dissolving 100 μL of n-butylamine in 5 mL of anhydrous ethanol and adding it to the system under stirring. The system was heated to 50 °C and stirred continuously for 2.5 h. After the reaction was complete, the system was cooled to room temperature, centrifuged to obtain the product, washed several times with anhydrous ethanol, and dried to obtain PS / PVP@AgNPs composite nanospheres.

[0070] SEM images of the composite nanospheres prepared in this comparative example are shown below. Figure 6 As shown in the image, the PS / PVP nanospheres are uniformly loaded with small-sized AgNPs on their surface, thus avoiding the aggregation of AgNPs.

[0071] Comparative Example 2

[0072] To compare the catalytic performance of the materials, the loading order of ZnONPs and AgNPs was changed to prepare polystyrene composite nanospheres co-supported with silver / zinc oxide nanoparticles. The preparation method is as follows:

[0073] 0.1 g of the PS / PVP nanospheres prepared in Example 1 were ultrasonically dispersed in 45 mL of anhydrous ethanol. 0.2 g of AgNO3 was added to the system, and the mixture was stirred at room temperature for 3 h to ensure complete dispersion of silver ions on the surface of the nanospheres. 100 μL of n-butylamine (dissolved in 5 mL of anhydrous ethanol) was slowly added to the system under stirring. The system was heated to 50 °C and stirred continuously for 2.5 h. After the reaction, the system was cooled to room temperature, centrifuged to obtain the product, and washed several times with anhydrous ethanol to obtain silver nanoparticle-loaded polystyrene composite nanospheres. The silver nanoparticle-loaded polystyrene composite nanospheres were dispersed in 3.5 mL of anhydrous ethanol to form a new system. 0.008 g of Zn(Ac)₂·2H₂O was weighed and added to the system, and the temperature was raised to 60 °C. The mixture was stirred continuously for 1 h to ensure complete dispersion of zinc ions on the surface of the nanospheres. To reduce zinc ions, 1.5 mL of an ethanol solution (58 mM) of NaOH was slowly added dropwise to the system under stirring. After the addition was complete, the system was stirred at 60 °C for 2 h. After the reaction was complete, the system was cooled to room temperature, centrifuged to obtain the product, washed several times with anhydrous ethanol, and dried in an oven to obtain the PS / PVP@Ag / ZnONPs composite nanosphere catalyst.

[0074] Experimental Example 1

[0075] Experiments on the degradation of 4-NP by NaBH4 using different catalysts.

[0076] Under sunlight irradiation, the position of the UV absorption peak of the system was first measured after diluting the 1 mL (3 mM) aqueous solution of 4-NP with deionized water to a final volume of 4 mL. Figure 6 The image shows that a standalone 4-NP solution exhibits a UV absorption peak at 317 nm. To demonstrate the effect of NaBH4 on 4-NP, under sunlight irradiation, 1 mL of 4-NP aqueous solution (3 mM) and 1 mL of NaBH4 aqueous solution (0.3 M) were mixed and shaken in a centrifuge tube, then diluted to 4 mL with deionized water before measuring the position of the UV absorption peak. Figure 7 The experiment showed that after 4-NP reacted with freshly prepared NaBH4 solution, 4-nitrophenolate ions were generated, and the 4-NP absorption peak shifted to 400 nm. After 12 minutes, NaBH4 still had no effect on the peak intensity at 400 nm, demonstrating that NaBH4 cannot reduce 4-NP without a catalyst. Therefore, the degradation of 4-NP by NaBH4 requires the addition of a catalyst.

[0077] To test the catalytic activity of each catalyst, the PS / PVP@AgNPs catalyst prepared in Comparative Example 1 was ultrasonically dispersed in water under sunlight to obtain a catalyst dispersion (1 mg / mL). Then, 2 mL of the catalyst dispersion from Comparative Example 1 was rapidly added to a mixture of 1 mL of 4-NP aqueous solution (3 mM) and 1 mL of NaBH4 aqueous solution (0.3 M). The changes in the absorption peak intensity of the system were tested at 1-min intervals after different catalytic times. Figure 7 b shows that after adding the PS / PVP@AgNPs catalyst, the absorption peak intensity at 400 nm gradually decreased, while a new absorption peak appeared at 300 nm. This is because the PS / PVP@AgNPs catalyzes the reduction of 4-nitrophenolate ions to generate 4-AP. The absorption peak intensity at 400 nm decreased by 78.3% within 3 minutes, and thereafter the peak intensity no longer changed significantly with increasing time. This indicates that AgNPs are well dispersed on the PS / PVP surface and exert their catalytic activity, but the single catalytic material limits the catalytic activity.

[0078] To overcome the above problems, under sunlight irradiation, this invention obtained a PS / PVP@Ag / ZnONPs composite nanosphere catalyst in Comparative Example 2, which was ultrasonically dispersed in water to obtain a catalyst dispersion (1 mg / mL). Then, 2 mL of the catalyst dispersion from Comparative Example 2 was rapidly added to a mixture of 1 mL of 4-NP aqueous solution (3 mM) and 1 mL of NaBH4 aqueous solution (0.3 M). The changes in the absorption peak intensity of the system after different catalytic times were tested at 10-second intervals. Figure 7 c shows that the absorption peak intensity at 400 nm decreased by 89% within 10 s, confirming the synergistic effect between AgNPs and ZnONPs. However, the catalytic activity still has limitations.

[0079] To further enhance catalytic activity, a PS / PVP@ZnO / AgNPs composite nanosphere catalyst, obtained in Example 5, was ultrasonically dispersed in water to obtain a catalyst dispersion (1 mg / mL) under sunlight irradiation. Then, 2 mL of this catalyst dispersion was rapidly added to a mixture of 1 mL (3 mM) of 4-NP aqueous solution and 1 mL (0.3 M) of NaBH4 aqueous solution. The changes in absorption peak intensity were measured at 10-second intervals after different catalytic times. Figure 7 The d-axis shows that the absorption peak intensity at 400 nm decreased by 99.2% within 10 s. Figure 8Figures a and b show the color change of the system before and after 10 seconds of catalyst application, visually demonstrating its ability to rapidly catalyze the degradation of most 4-NPs under sunlight alone. The difference in catalytic activity caused by the different loading order may be due to the later-loaded ZnONPs, which have no visible light photocatalytic activity, covering the existing AgNPs and thus reducing the active sites. Changing the loading order effectively avoids this situation; the later-loaded AgNPs are distributed on the outermost layer of the composite nanospheres and synergistically interact with the existing ZnONPs, thereby enhancing the catalytic activity. In this case, the molar amount of ZnONPs accounts for 3% of the molar amount of AgNPs.

[0080] Experimental Example 2

[0081] Catalytic cycle experiment of the composite catalyst prepared in Example 5.

[0082] To meet the industrial requirements for catalyst stability, this invention conducted a catalytic cycle experiment on the PS / PVP@ZnO / AgNPs composite nanosphere catalyst prepared in Example 5. The experimental and testing procedures were the same as those in the PS / PVP@ZnO / AgNPs catalytic experiment in Example 1. After use, the catalyst was collected by centrifugation, washed, and reused. Figure 9 The data showed that after 6 cycles of reuse, the degradation rate of 4-NP remained stable at around 99%. However, with the increase in the number of cycles, the time required to reach the highest degradation rate increased from 10 seconds to about 180 seconds. This may be due to the loss of materials during the centrifugal recycling process.

[0083] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A polystyrene composite nanosphere supported on zinc oxide / silver nanoparticles, characterized in that, The composite nanospheres are polyvinylpyrrolidone-styrene-acrylic acid nanospheres with zinc oxide nanoparticles and silver nanoparticles loaded on the surface of the polyvinylpyrrolidone-styrene-acrylic acid nanosphere carrier and the surface of the zinc oxide nanoparticles; the polyvinylpyrrolidone-styrene-acrylic acid nanospheres are styrene-acrylic acid copolymer nanospheres with polyvinylpyrrolidone coated on the surface. The method for preparing the zinc oxide / silver nanoparticle-supported polystyrene composite nanospheres includes the following steps: (1) Dissolve the initiator and polyvinylpyrrolidone in deionized water, add styrene and acrylic monomer, disperse fully, then polymerize and dry to obtain polyvinylpyrrolidone-styrene-acrylic nanospheres; (2) Polyvinylpyrrolidone-styrene-acrylic acid nanospheres were fully dispersed in anhydrous ethanol, a Zn source was added, and the mixture was thoroughly mixed. A reducing agent was added, and the mixture was subjected to a reduction reaction. After centrifugation and washing, zinc oxide-supported polystyrene composite nanospheres were obtained. The mass ratio of the Zn source to the polyvinylpyrrolidone-styrene-acrylic acid nanospheres was 0.06-0.1:

1. The reducing agent was a NaOH ethanol solution with a concentration of 55-60 mmol / L. (3) The zinc oxide-loaded polystyrene composite nanospheres are fully dispersed in anhydrous ethanol, Ag source is added, and the mixture is thoroughly mixed. A reducing agent is added, and after reduction reaction, the mixture is centrifuged, washed, and dried to obtain zinc oxide / silver nanoparticle-loaded polystyrene composite nanospheres. The mass ratio of the Ag source to the mass ratio of polyvinylpyrrolidone-styrene-acrylic acid nanospheres in step (2) is 1-3:

1. The reducing agent is an ethanol solution of n-butylamine.

2. The polystyrene composite nanospheres supported on zinc oxide / silver nanoparticles according to claim 1, characterized in that, The particle size of the polyvinylpyrrolidone-styrene-acrylic acid nanospheres is 180-220 nm.

3. The polystyrene composite nanospheres supported on zinc oxide / silver nanoparticles according to claim 1, characterized in that, Step (1) includes one or more of the following conditions: i. The initiator is potassium persulfate; the mass of the initiator is 2-4% of the mass of styrene. ii. The mass of polyvinylpyrrolidone is 0.01-0.06% of the mass of deionized water; iii. The mass ratio of styrene, acrylic acid, and polyvinylpyrrolidone is 3-4:1:0.02-0.11; iv. The polymerization reaction conditions are as follows: under inert gas protection and stirring, the polymerization reaction is carried out at 70-80℃ for 10-14 hours, and then at 85-90℃ for 0.5-1 hours; the inert gas is nitrogen or argon.

4. The polystyrene composite nanospheres supported on zinc oxide / silver nanoparticles according to claim 1, characterized in that, Step (2) includes one or more of the following conditions: i. The mass ratio of polyvinylpyrrolidone-styrene-acrylic acid nanospheres to the volume ratio of anhydrous ethanol is 0.01-0.1 g / mL; ii. The Zn source is Zn(Ac)2·2H2O; iii. After adding the Zn source, stir at 55-65℃ for 0.5-2 hours to ensure thorough mixing; iv. The mass ratio of NaOH to zinc source is 0.4-0.5:1; the reducing agent is added to the system dropwise. v. The reduction reaction temperature is 50-70℃, the reduction reaction time is 1-3h, and the reduction reaction is carried out under stirring conditions.

5. The polystyrene composite nanospheres supported on zinc oxide / silver nanoparticles according to claim 1, characterized in that, Includes one or more of the following conditions: i. The mass ratio of polyvinylpyrrolidone-styrene-acrylic acid nanospheres in step (2) to the volume ratio of anhydrous ethanol in step (3) is 0.002-0.003 g / mL; ii. In step (3), the Ag source is AgNO3; iii. In step (3), after adding the Ag source, stir at room temperature for 2-4 hours to ensure thorough mixing; iv. In step (3), the volume ratio of n-butylamine to ethanol in the reducing agent is 1:45-55; the mass ratio of Ag source to reducing agent is 1-3:1 g / mL. v. In step (3), the reduction reaction temperature is 40-60℃, the reduction reaction time is 1-3h, and the reduction reaction is carried out under stirring conditions.

6. The application of polystyrene composite nanospheres supported by zinc oxide / silver nanoparticles as described in any one of claims 1-5, as a catalyst for the catalytic degradation of p-nitrophenol in wastewater by NaBH4.

7. The application according to claim 6, characterized in that, The catalytic condition was visible light irradiation.

8. The application according to claim 6, characterized in that, The application method includes the following steps: fully dispersing the catalyst and sodium borohydride in wastewater containing p-nitrophenol, and then degrading p-nitrophenol under visible light irradiation.

Citation Information

Patent Citations

  • Preparation and application of nano-silver magnetic polystyrene microspheres

    CN106268958A

  • Preparation method of substrate for improving Raman scattering effect on surface of zinc oxide wrapped by silver nanoparticles

    CN108459003A